AC‐1001 H3 CDR peptide induces apoptosis and signs of autophagy in vitro and exhibits antimetastatic activity in a syngeneic melanoma model. Issue 9 (15th July 2016) - Rabaça, Aline N.; Arruda, Denise C.; Figueiredo, Carlos R.; Massaoka, Mariana H.; Farias, Camyla F.; Tada, Dayane B.; Maia, Vera C.; Silva Junior, Pedro I.; Girola, Natalia; Real, Fernando; Mortara, Renato A.; Polonelli, Luciano; et al.
Abstract : Antibody‐derived peptides modulate functions of the immune system and are a source of anti‐infective and antitumor substances. Recent studies have shown that they comprise amino acid sequences of immunoglobulin complementarity‐determining regions, but also fragments of constant regions. VH CDR3 of murine mAb AC‐1001 displays antimetastatic activities using B16F10‐Nex2 murine melanoma cells in a syngeneic model. The peptide was cytotoxic in vitro in murine and human melanoma cells inducing reactive oxygen species (ROS) and apoptosis by the intrinsic pathway. Signs of autophagy were also suggested by the increased expression of LC3/LC3II and Beclin 1 and by ultrastructural evidence. AC‐1001 H3 bound to both G‐ and F‐actin and inhibited tumor cell migration. These results are important evidence of the antitumor activity of Ig CDR‐derived peptides. Abstract : Antibody‐derived peptides are a source of anti‐infective and antitumor agents. The VH CDR3 of antiblood group‐A monoclonal antibody AC‐1001, which displays antimetastatic activity against melanoma cells, induces reactive oxygen species and apoptosis in tumor cells. Signs of autophagy preceded apoptosis. The CDR3 bound to β‐actin and inhibited cell migration. Its cytotoxic effects are independent of antibody specificity.